PELATIHAN ADMINISTRASI USAHA DAN DIVERSIFIKASI PRODUK OLAHAN PISANG PADA KELOMPOK USAHA PISANG GORENG DI KELURAHAN MALALAYANG DUA, KOTA MANADO - Christien Karambut; Jufrina Mandulangi; Iyam L. Dua (JURNAL DAYA-MAS, 2022)
Recording of business finances is very necessary in running a business. By not having a business financial record, you cannot know the profits or losses obtained. In addition, they cannot make good financial planning. Based on the results of interviews, it was found that most of the business actors did not understand how to record sales reports, were unable to calculate daily, weekly or monthly profits. Sales reports were not recorded in a consistent and structured manner. In addition, problems in the effectiveness of the use of raw materials, there is no solution for processing raw materials (bananas) that are too ripe other than being thrown away, causing waste.